Porosity Defect Analysis in ST 37 Steel Welding Joints Using the Dye Penetrant Method - Wari, Alan; Nurdin, Hendri; Ya, Kyaw Zay (Universitas Negeri Padang, 2020)
The procedures in the world of welding all look simple, but all welding that looks simple must have extensive knowledge in accordance with the definition of welding. This welding is a permanent connection technique, when the welding process takes place the results do not always meet the quality standards that have been determined. The cause of the welding results that do not meet the quality standards in the form of dirt on the material when before welding and so forth. The purpose of this study is that the specimen specimens are accepted according to the welding institute's standard acceptance criteria (TWI) This research uses st 37 steel by using SMAW welding electrodes LB 52U (E 7016) diameter 2.6mm for root, and LB 52U (E 7016) diameter 3.2 for fillers and caping with welding position 1G. Testing of welding results is carried out by the non destructive test of the dye penetrant method whose inspection results are determined based on the standard ASME. The results of this test study discontinuity in the form of porosity on the surface of the welding results in specimen 1, namely material contaminated by dirt, there are porosity defects scattered with a length of 6mm and porosity of 10mm so based on the standard TWI both test specimens were declared rejected, and in specimen 2, material that was not contaminated with impurities, there were porosity defects of 2mm and 2.5mm so that according to the standards of the two specimens the test was accepted. For the results of welding defects that are rejected can still be corrected by linking to the defects that, and can be done welding again.